Mobile application for localisation using bluetooth - Chan, Cepheus Sheng Ren (2015)
Mobile applications have given mobile phones of present day more use-cases beyond sending messages and making calls. They bring new functionality and methods for the user to interact with his/her device. Bluetooth beacons are small, lightweight transmitters that can be used as a point of reference for mobile devices. By receiving signals from the beacons, a mobile device can locate its position or use it as a point of reference. In my project, I seek to expand the usage of bluetooth beacons through the use of mobile applications. By identifying each bluetooth beacon and referencing them to landmarks or objects, the application will display different information to the user. A secondary goal is to enhance the experience of the users when their devices reacts according to detected bluetooth beacons, so as to create an application that interacts with the real world. This project is developed to encourage users and event/venue organisers to explore and implement the beacon technology. The purpose of this report is to record the procedures and results of developing iOS applications that make use of beacons. In the event that another person takes over this project, this report can be used as a guide to understand and begin developing beacon-based applications.